2010
DOI: 10.3109/14767050903366119
|View full text |Cite
|
Sign up to set email alerts
|

Serum and plasma determination of angiogenic and anti-angiogenic factors yield different results: The need for standardization in clinical practice

Abstract: Objective The importance of an anti-angiogenic state as a mechanism of disease in preeclampsia is now recognized. Assays for the determination of concentrations of soluble vascular endothelial growth factor receptor (sVEGFR)-1, sVEGFR-2, placental growth factor (PlGF) and soluble endoglin (sEng) have been developed for research and clinical laboratories. A key question is whether these factors should be measured in plasma or serum. The purpose of this study was to determine if there are differences in the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…Similar results have been described for other circulating proteins such as VEGF [34]. Also, Oggè G. et al reported comparable levels of PGF in both the plasma and serum of women with a normal pregnancy in the first, second and third trimesters [35] suggesting that the detected difference in our population data may not be ascribable to the source of the PGF measurements. Moreover, in our work, we have found that the environmental and genetic factors have a similar effect in both study samples suggesting that the difference in median levels between the two populations could be related to the effect of other factors able to influence the PGF levels.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been described for other circulating proteins such as VEGF [34]. Also, Oggè G. et al reported comparable levels of PGF in both the plasma and serum of women with a normal pregnancy in the first, second and third trimesters [35] suggesting that the detected difference in our population data may not be ascribable to the source of the PGF measurements. Moreover, in our work, we have found that the environmental and genetic factors have a similar effect in both study samples suggesting that the difference in median levels between the two populations could be related to the effect of other factors able to influence the PGF levels.…”
Section: Discussionsupporting
confidence: 90%
“…The sensitivity and coefficients of variation for these assays are described in Table I. Validation of these assays has been previously described [101]. …”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of the assays were as follows: PlGF, 9.52 pg/ml; sVEGFR-2, 19.01 pg/ml; sEng, 0.08 ng/ml and sVEGFR-1, 16.97 pg/ml. The validation of these assays has been described in previous studies [89]. …”
Section: Methodsmentioning
confidence: 99%